Study of Synergistic Effects of Herbal Meniran (Phyllanthus Niruri L) and Sambiloto (Andrographis Paniculata) as A Substitute Commercial Additive Feed to Improve Immunity Response and Free Chicken Egg Production - Puji Astuti; Heru Suripta; Diwi Acita Irawati (Postgraduate, University of Mataram, 2023)
This study aims to look at the immune response and egg production of free-range chickens after ND vaccination by administering meniran and Sambiloto extracts. The design used was a completely randomized design. Data on egg production were analyzed using analysis of variance and data on antibody and lymphocyte titers were analyzed descriptively. The results showed that on D+7 after vaccination, there was an increase in ND antibody and lymphocyte titers and in vaccinated chickens the ND titer was in a protective condition (â‰¥log26), whereas in non-vaccinated chickens, the ND titer and lymphocyte levels were in a less protective condition. On H+28 after the vaccine only the vaccine treatment showed a protective condition, but the administration of meniran and Sambilotol extracts was able to maintain the titer rate longer than without giving Meniran and Sambiloto extracts. Drinking water consumption (Sig.941), feed consumption (Sig.890), egg production (Sig.480) and feed conversion (sig.558) showed no difference. Based on the results of the study, the treatment of vaccines and extracts of meniran and Sambiloto gave a better immune response than without being vaccinated. Administration of meniran and Sambiloto extracts was able to maintain the level of immunity compared to no control.